2020
DOI: 10.1074/mcp.ra119.001808
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Phosphorylation Complex Regulates NLRP3 Inflammasome Activation and Predicts Patient Survival in Nasopharyngeal Carcinoma

Abstract: We previously reported that tumor inflammasomes play a key role in tumor control and act as favorable prognostic markers in nasopharyngeal carcinoma (NPC). Activated inflammasomes frequently form distinguishable specks and govern the cellular secretion of IL-1β. However, we know little about the biological and biochemical differences between cells with and without apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC) speck formation. In this study, we used proteomic iTRAQ analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…Other previous studies indicated that mitochondrial dysfunction also plays a vital role in NLRP3 inflammasome activation. Both mitochondrial reactive oxygen species and membrane proteins are involved in activation of the NLRP3 inflammasome (Kim et al, 2018b;Chung et al, 2019). In our study, we observed that NLRP3 localized with TOM20, a mitochondrial protein, as well as ultrastructural damage in mitochondria.…”
Section: Discussionsupporting
confidence: 56%
“…Other previous studies indicated that mitochondrial dysfunction also plays a vital role in NLRP3 inflammasome activation. Both mitochondrial reactive oxygen species and membrane proteins are involved in activation of the NLRP3 inflammasome (Kim et al, 2018b;Chung et al, 2019). In our study, we observed that NLRP3 localized with TOM20, a mitochondrial protein, as well as ultrastructural damage in mitochondria.…”
Section: Discussionsupporting
confidence: 56%
“…As in ammatory storms may promote the carcinogenesis (32,33), they may have relationships with cancer formation. In recent years, in ammasomes have been reported with higher or lower levels in HNCs, especially NLRP3 (20,21,23,(29)(30)(31) and AIM2 (22)(23)(24). However, no agreement has been reached on the relationships between in ammasomes and the prognosis of HNC.…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 98%
“…Among them, in ammasomes are also linked with head and neck cancers. However, although it is reported that some in ammasomes were upregulated in certain kinds of head and neck cancers (20), indicating a poorer prognosis (21), some were unchanged (22) and others even were favorable prognostic markers (23,24). They may have contradictory functions in promoting antitumor immuno-microenvironment and triggering oncogenic activities (23).…”
Section: Introductionmentioning
confidence: 98%
“…The in vivo ASC-speck formation within blood leukocytes is a distinguishing feature of inflammasome formation and permits a direct and quantitative study of blood samples by flow cytometry. This assay was well validated ( 30 32 ) and has been implemented previously ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%